Beyond gender role stereotypes – the changing view of women in IT managerial positions - Sołek-Borowska, Celina (Contemporary organisation and management. Challenges and trends, 2020)
The attraction of skilled and competent women to traditionally male dominated occupations, and their retention, have now become a great concern for today’s organizations. Not enough is known about the challenges faced by women professionals who possess the credentials, skills and knowledge that would allow them to be considered, alongside their male counterparts, for top-rank positions. Therefore, the purpose of the following paper is to identify and delineate the barriers for women in IT managerial positions. The research is based on 10 semi-structured interviews with women who occupy IT managerial positions. Participants were self-recruited following a call for participation in research posted to graduate students at Warsaw School of Economics. Findings show that the IT industry is predominantly masculine, and women are expected to perform roles similar to their male counterparts. The study identified different strategies used by women to compromise their gender identities and fit within their work environments.